IDENTIFIKASI SIFAT FISIKA TANAH DAN STATUS SODIUM PADA LAHAN MINA PADI DI DESA SIDONDO I KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Japar, Karmila; Hasanah, Uswah; Toana, Moh. Rizqi Chaldun (Fakultas Pertanian, Universitas Tadulako, 2023)
Mina padi represents a polyculture system that combines fish farming with paddy rice cultivation. In situations where there is limited irrigation water, this arrangement often transitions into a dryland cropping system. The primary objective of this study is to assess various soil characteristics and the sodium levels in dried mina wetland rice fields located in Sidondo I Village, Sigi Biromaru District, Sigi Regency. The findings revealed that the mina padi fields exhibited a range of textures, including loamy loam, sandy loam, and loam. Permeability varied from slow (0.39 cm/hour) to very fast (37.11 cm/h), while soil bulk density ranged from medium (1.37 g/cm3) to heavy (1.73 g/cm3). Porosity values ranged between slightly poor (48.3%) to poor (40.0%), organic matter content spanned from low (1.53%) to medium (3.44%), and sodium levels ranged from relatively low (0.36 Na-dd (cmol (+) kg-1) to very high (10.42 Na-dd (cmol (+) kg-1).